Evaluation of a 3D-printed total knee arthroplasty using radiostereometric analysis: assessment of highly porous biological fixation of the tibial baseplate and metal-backed patellar component. (July 2019) - Sporer, S.; MacLean, L.; Burger, A.; Moric, M.
Abstract : Aims: Our intention was to investigate if the highly porous biological fixation surfaces of a new 3D-printed total knee arthroplasty (TKA) achieved adequate fixation of the tibial and patellar components to the underlying bone. Patients and Methods: A total of 29 patients undergoing primary TKA consented to participate in this prospective cohort study. All patients received a highly porous tibial baseplate and metal-backed patella. Patient-reported outcomes measures were recorded and implant migration was assessed using radiostereometric analysis. Results: Patient function significantly improved by three months postoperatively (p < 0.001). Mean difference in maximum total point motion between 12 and 24 months was 0.021 mm (-0.265 to 0.572) for the tibial implant and 0.089 mm (-0.337 to 0.758) for the patellar implant. The rate of tibial and patellar migration was largest over the first six postoperative weeks, with no changes in mean tibia migration occurring after six months, and no changes in mean patellar migration occurring after six weeks. One patellar component showed a rapid rate of migration between 12 and 24 months. Conclusion: Biological fixation appears to occur reliably on the highly porous implant surface of the tibial baseplate and metal-backed patellar component. Rapid migration after 12 months was measured for one patellar component. Further investigation is required to assess the long-term stability of the 3D-printed components and to determine if the high-migrating components achieve fixation. Cite this article: Bone Joint J 2019;101-B(7 Supple C):40–47